Kebijakan Pemerintah Vietnam Dalam Mengatasi Emisi Gas Rumah Kaca - Primanurita Nungky Antari ; Muharjono Muharjono (Jurnal Paradigma, 2015)
Peoples known climate change as a global problem, nowadays almost peoples around the world impacted by Climate Change. Climate Change caused by the raising of greenhouse gas (ghg) concentration in the atmosfer. GHG is term which refers to several gases such as Carbondioxide (CO2), Sulfur Hexa ouride (SF6), Methane (CH4), Hidro uorocarbon (HFC), Per uorocarbon (PFC), and N2O. Climate change has several impact such as sea level rise, global warming and extreme climate. Vietnam is considered as one of the countries most affected by climate change. According World Bank survey Vietnam has been ranked among the ve countries likely to be most affected by climate change.